Gender-Based Analysis of Students’ Ability in Answering Factual and Vocabulary-in-Context Questions of the TOEFL-Like Reading Comprehension Test - Cahya Destiyanti; Muhammad Amin; Lalu Jaswadi Putera (LP2M STIT Palapa Nusantara, 2021)
This study was aimed to find out whether or not there was a significant difference between male and female students’ ability in answering factual and vocabulary-in-context questions of the TOEFL-Like reading comprehension test. Secondary data analysis was utilized by taking reading comprehension test scores of twenty-one male and twenty-one female students of the English Education Program. Samples were selected using random sampling technique. Data were analyzed using independent sample t-test. Results showed that the t-values of sig. 2-tailed was higher than 0.05 in male and female students’ ability in answering both the factual questions (0.267 > 0.05) and the vocabulary-in-context questions (0.837 > 0.05). The results revealed that there was no significant difference between male and female students’ ability in answering factual and vocabulary-in-context questions of the TOEFL-Like reading comprehension test.